Indonesian EFL Students’ Self-Regulated Learning Strategies for English Speaking - Trifosa, Maria; Keny, Anatasia; Bram, Barli (Universitas Muhammadiyah Mataram, 2025)
This study investigated self-regulated learning (SRL) strategies employed by Indonesian undergraduate students to enhance their English-speaking abilities. A quantitative research design was employed, with data collected from 30 undergraduate students through a modified Self-Regulated Motivation for Improving Speaking English as a Foreign Language (SRMIS-EFL) questionnaire. Descriptive statistical analyses, including mean scores and standard deviations, were conducted using SPSS to examine the extent to which four SRL factors, Task Value Evaluation, Regulation of Learning Environment, Regulation of Affect, and Regulation of Classroom Environment, were demonstrated. The findings indicated that Task Value Evaluation was the dominant factor supporting students’ speaking skills, while Regulation of Affect and Classroom Environment showed moderate engagement. These results suggest that cognitive, affective, and environmental strategies collectively influence students’ motivation and participation in English-speaking activities. Implications for teaching include designing meaningful speaking tasks, promoting peer collaboration, and creating supportive learning environments to strengthen students’ SRL and oral proficiency.